sebuah analisis kesalahan siswa dalam menjawab soal tes kemampuan pemahaman konsep - Aas Muhaiminah; Abas Hidayat (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2020)
Mathematics is the basic science of all sciences or the first step in learning other sciences, one of which is in education. In the world of education, especially the Indonesian state mathematics subjects ranked lowest in the TIMSS or PISA survey, it is suspected that one reason is the lack of understanding of students' concepts in mathematics. The purpose of this study was: to determine the level of understanding of students' mathematical concepts. This research is a test of the problem in accordance with the indicators in the ability to understand the concept. The population of this study is the tenth grade students at SMAN 1 Cilimus 2018/2019 school year. The sample of this study is class X IPS 5. Based on data analysis it can be concluded that: the ability of students' mathematical understanding is still lacking especially in class X IPS 5.